AN EFFICIENT REVIEW OF IDS IN MANET USING PSO - Dr Sharanabasappa C Gandage, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The region of Mobile Adhoc Network (MANET) has being a requested subject of examination for over 10 years on account of its appealing correspondence highlights related with different issues. Intrusion detection system (IDS) as we said before is an irreplaceable second line of resistance since conventional anticipation instruments are not sufficiently able to secure MANET. The trust highlights are removed from every node of MANET and these highlights are enhanced utilizing Particle Swarm Optimization (PSO) algorithm as highlight optimization strategy. These upgraded include sets are then arranged utilizing Neural Networks (NN) classifier which distinguishes the gatecrasher node. In this review paper we are elaborating the recent related reviews of intrusion detection systems in MANET by using the novel concept of artificial intelligence.